Metformin inhibits extracellular matrix accumulation, inflammation and proliferation of mesangial cells in diabetic nephropathy by regulating H19/miR-143-3p/TGF-β1 axis. (11th May 2020) - Xu, Jiang; Xiang, Ping; Liu, Linqing; Sun, Jianran; Ye, Shandong
Abstract: Objectives: Metformin (MET) has protective effect on diabetic nephropathy (DN). This study aims to demystify the mechanism of MET function in DN. Methods: Mouse glomerular membrane epithelial cell line SV40-MES-13 was treated with normal or high glucose combined with or without MET. The relationships among H19, miR-143-3p and TGF-β1 were evaluated by luciferase reporter assay. MTT assay was performed to detect cell proliferation. The levels of inflammatory factors were investigated by enzyme-linked immunosorbent assay. Quantitative real-time PCR and western blot were performed to examine gene and protein expression. Key Findings: H19 was up-regulated in the SV40-MES-13 cells after treated with high glucose, which was effectively repressed by MET treatment. MET promoted extracellular matrix accumulation, inflammation and proliferation in the SV40-MES-13 cells after treated with high glucose. These influences conferred by MET were abolished by H19 overexpression. H19 regulated TGF-β1 expression by sponging miR-143-3p. Furthermore, MET inhibited extracellular matrix accumulation, inflammation and proliferation by regulating H19/miR-143-3p/TGF-β1 axis. Conclusions: Our studies demonstrated that the protective effect of MET on DN was attributed to the inhibition of proliferation, inflammation and ECM accumulation in mesangial cells via H19/miR-143-3p/TGF-β1 axis, which suggested that the H19/miR-143-3p/TGF-β1 axis could be a valuable target for DN therapies.